Primary cerebellar haemorrhage: complications, treatment and outcome - Witsch, Jens; Neugebauer, Hermann; Zweckberger, Klaus; Jüttler, Eric (Clinical neurology and neurosurgery, 2013)
Given its anatomical proximity to the brainstem and the ventricular system, cerebellar haemorrhage may lead to immediate life-threatening complications such as brainstem compression and hydrocephalus, or to herniation through the foramen magnum or the tentorium. This situation mandates fast diagnosis and precise emergency treatment strategies. However, the treatment protocols in current use are based on little evidence and the indication criteria for surgical intervention are unclear. Early suboccipital decompressive surgery may be life-saving, but the potential risk involved is unnecessary if the haemorrhage is benign and can be managed conservatively or with insertion of an external ventricular drain. Deterioration of the patients’ state of consciousness has often been used as an indication for surgery, but clinical decline can be a fulminant process leading to death within a short time. Research on cerebellar haemorrhage so far has focused on identifying outcome predictors from which treatment algorithms can be derived. Large randomised controlled trials (RCTs) are lacking. However, RCTs are urgently needed, in order to improve the level of evidence, treatment decisions may be based on. Here, we review the available literature on complications, treatment and outcome of primary cerebellar haemorrhage (PCH). Finally we propose the design of a potential RCT.
Gesehen am 18.11.2021